Carbon-supported MnO2 catalyst, preparation method, modified diaphragm and lithium-sulfur battery
By using carbon-loaded MnO2 catalysts in lithium sulfur batteries, problems such as poor conductivity and large volume changes in lithium sulfur batteries are solved, and electrochemical performance and cycle stability are significantly improved, achieving more efficient sulfur reduction and oxidation reaction kinetics.
Patent Information
- Application Number
- CN202411568591.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The poor conductivity of sulfur and solid discharge products in lithium-sulfur batteries, the large volume changes during circulation, and the "shuttle effect" of soluble LiPSs and the slow sulfur reduction and oxidation reaction kinetics have limited the commercial application of lithium-sulfur batteries.
A uniformly dispersed carbon-laden MnO2 catalyst was developed. After mixing potassium permanganate, manganese sulfate, conductive carbon and deionized water in a specific proportion, conducting hydrothermal reaction, a catalyst with excellent conductivity and catalytic activity was prepared and used in lithium-sulfur batteries.
Through the use of carbon-laden MnO2 catalyst, the electrochemical performance of lithium sulfur batteries is significantly improved, including cycle stability and rate performance, suppressing the shuttle effect and improving the utilization rate of the active substance sulfur.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-sulfur batteries, and in particular to a carbon-supported MnO2 catalyst, a preparation method, a modified diaphragm, and a lithium-sulfur battery. Background Art
[0002] Lithium-sulfur (Li-S) batteries are considered to be the best alternative to future secondary batteries because of their high energy density (≈2600Wh kg -1 ), low cost and environmental protection. However, there are still many problems that limit the commercial application of lithium-sulfur batteries, such as the poor conductivity of sulfur and solid discharge products (Li2S / Li2S2), the large volume change of sulfur cathode during the cycle (≈80%), the "shuttle effect" of soluble LiPSs and the slow sulfur reduction oxidation reaction (SRR) kinetics and the volume expansion of the positive electrode during the reaction.
[0003] In order to solve these problems, catalysts are usually used to accelerate the conversion of LiPSs, which can effectively reduce the "shuttle effect" and accelerate the SRR kinetics. Sulfides, nitrides, phosphides and their heterostructures are widely used as catalysts. However, the poor conductivity of sulfur and solid-state discharge products (Li2S / Li2S2) and the expansion problem are still not effectively solved. Introducing materials with good conductivity and flexibility into lithium-sulfur batteries can improve conductivity and alleviate volume expansion problems.
[0004] Therefore, in order to solve the above problems, loading the catalyst onto conductive carbon black to form a new catalyst system is an effective solution for future catalyst design. Summary of the invention
[0005] In order to solve at least one of the above technical problems, a uniformly dispersed carbon-supported MnO2 catalyst is developed to prepare a lithium-sulfur battery with excellent electrical properties. The present application provides a carbon-supported MnO2 catalyst, a preparation method, a modified diaphragm and a lithium-sulfur battery.
[0006] On the one hand, the present application provides a carbon-supported MnO2 catalyst, which is prepared from potassium permanganate, manganese sulfate, conductive carbon and deionized water, wherein potassium permanganate, manganese sulfate, conductive carbon and deionized water are added in a ratio of 0.1mmol:0.1mmol:20mg~50mg:50ml.
[0007] Optionally, the conductive carbon is one or more combinations of graphite, conductive carbon black, Ketjen black, and biomass carbon.
[0008] In a second aspect, the present application provides a method for preparing the above-mentioned carbon-supported MnO2 catalyst, comprising the following steps:
[0009] S1. Add potassium permanganate, manganese sulfate, conductive carbon and deionized water into a reactor; place the reactor at 140°C for hydrothermal reaction for 1 hour;
[0010] S2, centrifugation washing 3 times with water and anhydrous ethanol respectively;
[0011] S3. Vacuum dry at 60℃~80℃ for 12h to obtain carbon-supported MnO2 catalyst.
[0012] Optionally, in S1, the heating rate is 5°C / min.
[0013] In a third aspect, the present application provides a modified diaphragm, comprising conductive carbon black, PVDF and the carbon-supported MnO2 catalyst described in claim 1; wherein the mass ratio of the carbon-supported MnO2 catalyst, the conductive carbon black and the PVDF is 1-3:5-8:1-3.
[0014] Optionally, the mass ratio of the carbon-supported MnO2 catalyst, the conductive carbon black and the PVDF is 2:7:1.
[0015] Fourthly, the present application provides a method for preparing the above-mentioned modified diaphragm, grinding the formulated amount of carbon-supported MnO2 catalyst, conductive carbon black and PVDF, adding NMP solvent and stirring to obtain a slurry, evenly coating the slurry on the diaphragm, and vacuum drying at 50°C for 12 hours to obtain the modified diaphragm.
[0016] Optionally, the diaphragm is a PP diaphragm.
[0017] In a fifth aspect, the present application provides a lithium-sulfur battery, comprising the modified diaphragm described above, wherein a side of the modified diaphragm coated with the slurry faces the positive electrode.
[0018] Optionally, the lithium-sulfur battery includes an electrode, and the preparation method of the electrode is: sulfur and conductive carbon black are mixed and ground in a mass ratio of 7:3, and kept at 155°C for 12 hours in a nitrogen atmosphere to obtain a C / S positive electrode; the C / S positive electrode, PVDF and CB are mixed, and a DMF solvent is added to form a uniform slurry, the slurry is coated on an aluminum foil, and vacuum dried at 60°C; the mass ratio of the C / S positive electrode, PVDF and CB is 5-8:1-2:1-3.
[0019] In summary, the present application includes at least one of the following beneficial technical effects:
[0020] 1. The present application uses conductive carbon as the growth substrate of MnO2, which ensures the conductivity and polarity of the catalyst, and at the same time ensures the rapid progress of the lithium ion migration process and the sulfur conversion catalytic process; and the conductive carbon and MnO2 can generate a built-in electric field, optimize the distribution of charges at the interface, and thus show a better catalytic activity;
[0021] 2. The synergistic effect of conductive carbon and MnO2 in the carbon-supported MnO2 catalyst can promote the rapid transformation and migration of LiPSs and induce their uniform deposition; the carbon-supported MnO2 catalyst can effectively promote the transformation kinetics of LiPSs, accelerate the transformation of S8 to Li2S during discharge, and accelerate the reduction electrochemical kinetics; in the charging process, it is beneficial to the conversion of Li2S to Li2S n conversion, accelerating the oxidation electrochemical kinetics, bidirectionally promoting the rapid conversion of LiPSs in lithium-sulfur batteries, inhibiting the shuttle effect, and improving the utilization rate of active sulfur and the electrochemical performance of lithium-sulfur batteries;
[0022] 3. The carbon-supported MnO2 catalyst prepared in this application is synthesized in a hydrothermal reaction and has low energy consumption;
[0023] 4. The lithium-sulfur battery prepared in this application has greatly improved cycle stability and rate performance, and the preparation process is simple and easy to operate, which is conducive to industrial production. DETAILED DESCRIPTION
[0024] The present application is further described in detail below with reference to the embodiments.
[0025] In the following examples of the present application, the main components involved, unless otherwise specified, were purchased from commercially available products.
[0026] The purity of potassium permanganate and manganese sulfate is analytical grade, and deionized water is homemade in the laboratory. The conductive carbon in the following embodiments of the present application exemplarily adopts conductive carbon black. Specific embodiments
[0028] Examples 1 to 4 are used to prepare carbon-supported MnO2 catalysts, and the details are as follows.
[0029] Example 1
[0030] This embodiment discloses a method for preparing a carbon-supported MnO2 catalyst.
[0031] Add 15.8 mg potassium permanganate, 15.1 mg manganese sulfate, 20 mg conductive carbon black and 50 ml deionized water into the reactor; heat to 140°C at a heating rate of 5°C / min and dry for 1 hour; wash by centrifugation with water and anhydrous ethanol for 3 times respectively; vacuum dry at 60°C for 12 hours to obtain a carbon-supported MnO2 catalyst.
[0032] Example 2
[0033] This embodiment discloses a method for preparing a carbon-supported MnO2 catalyst.
[0034] Add 15.8 mg potassium permanganate, 15.1 mg manganese sulfate, 30 mg conductive carbon black and 50 ml deionized water into the reactor; heat to 140°C at a heating rate of 5°C / min and dry for 1 hour; wash by centrifugation with water and anhydrous ethanol for 3 times respectively; vacuum dry at 60°C for 12 hours to obtain a carbon-supported MnO2 catalyst.
[0035] Example 3
[0036] This embodiment discloses a method for preparing a carbon-supported MnO2 catalyst.
[0037] Add 15.8 mg potassium permanganate, 15.1 mg manganese sulfate, 40 mg conductive carbon black and 50 ml deionized water into the reactor; heat to 140°C at a heating rate of 5°C / min and dry for 1 hour; wash by centrifugation with water and anhydrous ethanol for 3 times respectively; vacuum dry at 60°C for 12 hours to obtain a carbon-supported MnO2 catalyst.
[0038] Example 4
[0039] This embodiment discloses a method for preparing a carbon-supported MnO2 catalyst.
[0040] Add 15.8 mg potassium permanganate, 15.1 mg manganese sulfate, 50 mg conductive carbon black and 50 ml deionized water into the reactor; heat to 140°C at a heating rate of 5°C / min and dry for 1 hour; wash by centrifugation with water and anhydrous ethanol for 3 times respectively; vacuum dry at 60°C for 12 hours to obtain a carbon-supported MnO2 catalyst.
[0041] Comparative Example 1
[0042] This comparative example discloses a method for preparing a carbon-supported MnO2 catalyst.
[0043] 17.4 mg of MnO2 and 50 mg of conductive carbon black were mechanically mixed to obtain a carbon-supported MnO2 catalyst.
[0044] Examples 5 to 8 are used to prepare modified membranes, and the details are as follows.
[0045] Example 5
[0046] This embodiment discloses a method for preparing a modified membrane.
[0047] Take 60 mg of the carbon-supported MnO2 catalyst prepared in Example 1, 160 mg of conductive carbon black and 20 mg of PVDF (polyvinylidene fluoride), add them into a mortar for mixing and grinding, add an appropriate amount of NMP solvent and stir continuously for 12 hours to obtain a slurry.
[0048] The slurry was evenly coated on the Celgard-2400PP separator with a 200 μm scraper, and transferred to an oven for vacuum drying at 60° C. for 12 h to obtain a modified separator.
[0049] Example 6
[0050] This embodiment discloses a method for preparing a modified membrane.
[0051] Take 40 mg of the carbon-supported MnO2 catalyst prepared in Example 1, 140 mg of conductive carbon black and 20 mg of PVDF (polyvinylidene fluoride), add them into a mortar for mixing and grinding, add an appropriate amount of NMP solvent and stir continuously for 12 hours to obtain a slurry.
[0052] The slurry was evenly coated on the Celgard-2400PP separator with a 200 μm scraper, and transferred to an oven for vacuum drying at 60° C. for 12 h to obtain a modified separator.
[0053] Example 7
[0054] This embodiment discloses a method for preparing a modified membrane.
[0055] Take 40 mg of the carbon-supported MnO2 catalyst prepared in Example 1, 140 mg of conductive carbon black and 20 mg of PVDF (polyvinylidene fluoride), add them into a mortar for mixing and grinding, add an appropriate amount of NMP solvent and stir continuously for 12 hours to obtain a slurry.
[0056] The slurry was evenly coated on the Celgard-2400PP separator with a 200 μm scraper, and transferred to an oven for vacuum drying at 60° C. for 12 h to obtain a modified separator.
[0057] Example 8
[0058] This embodiment discloses a method for preparing a modified membrane.
[0059] Take 20 mg of the carbon-supported MnO2 catalyst prepared in Example 1, 100 mg of conductive carbon black and 60 mg of PVDF (polyvinylidene fluoride), add them into a mortar for mixing and grinding, add an appropriate amount of NMP solvent and stir continuously for 12 hours to obtain a slurry.
[0060] The slurry was evenly coated on the Celgard-2400PP separator with a 200 μm scraper, and transferred to an oven for vacuum drying at 60° C. for 12 h to obtain a modified separator.
[0061] Comparative Example 2
[0062] This comparative example discloses a method for preparing a modified diaphragm.
[0063] Take 40 mg of the carbon-supported MnO2 catalyst prepared in Comparative Example 1, 140 mg of conductive carbon black and 20 mg of PVDF (polyvinylidene fluoride), add them into a mortar for mixing and grinding, add an appropriate amount of NMP solvent and stir continuously for 12 hours to obtain a slurry.
[0064] The slurry was evenly coated on the Celgard-2400PP separator with a 200 μm scraper, and transferred to an oven for vacuum drying at 60° C. for 12 h to obtain a modified separator.
[0065] Examples 9 to 12 are used to prepare lithium-sulfur batteries, and the details are as follows.
[0066] Example 9
[0067] The cut positive electrode sheet and separator were placed in a glove box, and then the CR2032 button cell was assembled in the order of positive electrode shell, positive electrode sheet, electrolyte, modified separator prepared in Example 5, electrolyte, negative electrode sheet, gasket, spring and negative electrode shell. The electrolyte used was 1M LiTFSI, DME:DOL=1:1V%, and 1M LiNO3.
[0068] The preparation method of the positive electrode sheet is as follows: S and CB are mixed and ground in a mass ratio of 7:3, and the mixture is kept at 155°C for 12 hours under a nitrogen atmosphere to obtain a C / S positive electrode; the C / S positive electrode, PVDF and CB are mixed in a mass ratio of 5:2:3, and a DMF solvent is added to form a uniform slurry, the slurry is coated on an aluminum foil, and vacuum dried at 60°C.
[0069] The charge and discharge performance of the button battery prepared in this example was tested at room temperature using a LandCT2001A battery testing system. After three cycles of activation, the first cycle discharge capacity was 1012.7 mAh / g at 1C, and after 1000 cycles, the capacity remained at 552.23 mAh / g.
[0070] Example 10
[0071] The cut positive electrode sheet and separator were placed in a glove box, and then a CR2032 button cell was assembled in the order of positive electrode shell, positive electrode sheet, electrolyte, modified separator prepared in Example 6, electrolyte, negative electrode sheet, gasket, spring and negative electrode shell. The electrolyte used was 1M LiTFSI, DME:DOL=1:1V%, and 1M LiNO3.
[0072] The preparation method of the positive electrode sheet is as follows: S and CB are mixed and ground in a mass ratio of 7:3, and the mixture is kept at 155°C for 12 hours under a nitrogen atmosphere to obtain a C / S positive electrode; the C / S positive electrode, PVDF and CB are mixed in a mass ratio of 8:1:1, and a DMF solvent is added to form a uniform slurry, the slurry is coated on an aluminum foil, and vacuum dried at 60°C.
[0073] The charge and discharge performance of the button battery prepared in this example was tested at room temperature using a LandCT2001A battery testing system. After three cycles of activation, the first cycle discharge capacity was 1033.25 mAh / g at 1C, and after 1000 cycles, the capacity remained at 563.02 mAh / g.
[0074] Embodiment 11
[0075] The cut positive electrode sheet and separator were placed in a glove box, and then a CR2032 button cell was assembled in the order of positive electrode shell, positive electrode sheet, electrolyte, modified separator prepared in Example 7, electrolyte, negative electrode sheet, gasket, spring and negative electrode shell. The electrolyte used was 1M LiTFSI, DME:DOL=1:1V%, and 1M LiNO3.
[0076] The preparation method of the positive electrode sheet is as follows: S and CB are mixed and ground in a mass ratio of 8:1, and the mixture is kept at 155°C for 12 hours under a nitrogen atmosphere to obtain a C / S positive electrode; the C / S positive electrode, PVDF and CB are mixed in a mass ratio of 5:2:3, and a DMF solvent is added to form a uniform slurry, the slurry is coated on an aluminum foil, and vacuum dried at 60°C.
[0077] The charge and discharge performance of the button battery prepared in this example was tested at room temperature using a LandCT2001A battery testing system. After three cycles of activation, the first cycle discharge capacity was 1032.02 mAh / g at 1C, and after 1000 cycles, the capacity remained at 553.20 mAh / g.
[0078] Example 12
[0079] The cut positive electrode sheet and separator were placed in a glove box, and then a CR2032 button cell was assembled in the order of positive electrode shell, positive electrode sheet, electrolyte, modified separator prepared in Example 8, electrolyte, negative electrode sheet, gasket, spring and negative electrode shell. The electrolyte used was 1M LiTFSI, DME:DOL=1:1V%, and 1M LiNO3.
[0080] The preparation method of the positive electrode sheet is as follows: S and CB are mixed and ground in a mass ratio of 8:1, and the mixture is kept at 155°C for 12 hours under a nitrogen atmosphere to obtain a C / S positive electrode; the C / S positive electrode, PVDF and CB are mixed in a mass ratio of 8:1:1, and a DMF solvent is added to form a uniform slurry, the slurry is coated on an aluminum foil, and vacuum dried at 60°C.
[0081] The charge and discharge performance of the button battery prepared in this embodiment was tested at room temperature using a LandCT2001A battery testing system. After three cycles of activation, the first cycle discharge capacity was 1031.6 mAh / g at 1C, and after 1000 cycles, the capacity remained at 557.56 mAh / g.
[0082] Comparative Example 3
[0083] The cut positive electrode sheet and separator were placed in a glove box, and then a CR2032 button cell was assembled in the order of positive electrode shell, positive electrode sheet, electrolyte, modified separator prepared in Example 6, electrolyte, negative electrode sheet, gasket, spring and negative electrode shell. The electrolyte used was 1M LiTFSI, DME:DOL=1:1V%, and 1M LiNO3.
[0084] The preparation method of the positive electrode sheet is as follows: S and CB are mixed and ground in a mass ratio of 7:3, and the mixture is kept at 155°C for 12 hours under a nitrogen atmosphere to obtain a C / S positive electrode; the C / S positive electrode, PVDF and CB are mixed in a mass ratio of 8:1:1, and a DMF solvent is added to form a uniform slurry, the slurry is coated on an aluminum foil, and vacuum dried at 60°C.
[0085] The charge and discharge performance of the button battery prepared in this example was tested at room temperature using a LandCT2001A battery testing system. After three cycles of activation, the first cycle discharge capacity was 823.7 mAh / g at 1C, and after 1000 cycles, the capacity remained at 411.3 mAh / g.
[0086] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A carbon-supported MnO2 catalyst, characterized in that: The method is prepared from potassium permanganate, manganese sulfate, conductive carbon and deionized water, wherein potassium permanganate, manganese sulfate, conductive carbon and deionized water are added in a ratio of 0.1 mmol: 0.1 mmol: 20 mg to 50 mg: 50 ml.
2. The carbon-supported MnO2 catalyst according to claim 1, characterized in that The conductive carbon is one or more combinations of graphite, conductive carbon black, Ketjen black and biomass carbon.
3. A method for preparing the carbon-supported MnO2 catalyst according to claim 1, characterized in that: The following steps are involved: S1. Add potassium permanganate, manganese sulfate, conductive carbon and deionized water into a reactor; place the reactor at 140°C for hydrothermal reaction for 1 hour; S2, centrifugation washing 3 times with water and anhydrous ethanol respectively; S3. Vacuum dry at 60℃~80℃ for 12h to obtain carbon-supported MnO2 catalyst.
4. The preparation method according to claim 3, characterized in that: In S1, the heating rate is 5°C / min.
5. A modified diaphragm, characterized in that: The invention comprises conductive carbon black, PVDF and the carbon-supported MnO2 catalyst as claimed in claim 1; wherein the mass ratio of the carbon-supported MnO2 catalyst, the conductive carbon black and the PVDF is 1-3:5-8:1-3.
6. The modified membrane according to claim 5, characterized in that The mass ratio of carbon-supported MnO2 catalyst, conductive carbon black and PVDF is 2:7:
1.
7. A method for preparing the modified membrane according to claim 5, characterized in that: The carbon-supported MnO2 catalyst, conductive carbon black and PVDF in the formulated amount were ground, NMP solvent was added and stirred to obtain slurry, the slurry was evenly coated on the diaphragm, and the modified diaphragm was obtained after vacuum drying at 50°C for 12 hours.
8. The preparation method according to claim 7, characterized in that: The diaphragm is a PP diaphragm.
9. A lithium-sulfur battery, characterized in that: The modified separator comprises the modified separator as claimed in claim 5, wherein the side of the modified separator coated with the slurry faces the positive electrode.
10. The lithium-sulfur battery according to claim 9, characterized in that: The invention comprises an electrode, wherein the preparation method of the electrode is as follows: sulfur and conductive carbon black are mixed and ground in a mass ratio of 7:3, and the mixture is kept at 155°C for 12 hours under a nitrogen atmosphere to obtain a C / S positive electrode; the C / S positive electrode, PVDF and CB are mixed, and a DMF solvent is added to form a uniform slurry, the slurry is coated on an aluminum foil, and the mixture is vacuum dried at 60°C to obtain the obtained slurry; the mass ratio of the C / S positive electrode, PVDF and CB is 5-8:1-2:1-3.
Citation Information
Patent Citations
Modified manganese dioxide catalyst, functional diaphragm and preparation method and application thereof
CN116315448A
Manganese-based oxide catalyst, modified diaphragm slurry, modified diaphragm and lithium-sulfur battery
CN117299112A